'See First, Think Later, then Test': How Children's Perspectives can Improve Economic Research - Orkin, K (Macmillan Publishers Ltd, 2011)
Economists study many aspects of children’s lives. They have been criticised by childhood studies researchers for failing to recognise children as agents, despite evidence that children act, within social constraints, to achieve outcomes they prefer. Childhood studies researchers also argue that economists neglect to use methods which capture children’s perspectives on their lives, although evidence shows adult caregivers often describe children’s views or behaviours inaccurately. Economists largely ignore such criticisms. I describe qualitative research on child time allocation in rural Ethiopia. I argue that in this research, children’s perspectives, gathered through qualitative methods, challenged current microeconomic theory and suggested improvements to it. Insights from qualitative work demonstrated the inaccuracy of two assumptions made in standard theory models: that children cannot make decisions about their time and that families have uniform preferences about children’s work. Qualitative research also highlighted factors not captured by theory which children and parents said affected decisions.